EFEKTIVITAS PROGRAM TRANSMIGRASI DALAM MENGATASI KEMISKINAN: STUDI KASUS RASAU JAYA (1971-1980) - Yafi, Reyhan Ainun; Setiawan, Adi (Handep: Jurnal Sejarah dan Budaya, 2024)
This article looks into the transmigration programme in Rasau Jaya from 1971 to 1980, focusing on the circumstances and socio-economic challenges that transmigrants dealt with. Transmigration was one of the New Order government programmes to address the overcrowding and poverty issues. This research aims to analyse how effectively the transmigration program in Rasau Jaya can address the issue of poverty. The study adopted the historical method, utilising various sources such as documents from Dinas Transmigrasi Provinsi Kalimantan Barat, Direktorat Penelitian dan Persiapan, Direktorat Jenderal Transmigrasi, newspapers and some other relevant literature. This article highlights the poverty experienced by transmigrants, a topic often overlooked in previous studies. The findings suggest that the transmigration program in Rasau Jaya has fallen short of its goal of alleviating poverty. Three main factors contribute to this shortfall, including inadequate government preparation, the basic skills of the transmigrants, and the ecological conditions prevalent in the Rasau Jaya area. As a result, transmigrants in Rasau Jaya are compelled to seek employment outside of agriculture, taking on roles as construction workers or timber workers and even as homeless individuals doing various odd jobs.